Characterization and Alumina Leachability of 12CaO·7Al2O3 with Different Holding Times. (17th July 2014) - Sun, Hui-lan; Wang, Bo; Zhang, Jian-xin; Zong, Shu-feng
Abstract : The effect of synthesis time on phase compositions, lattice constant, average grain size, preferred orientation, and surface morphology of 12CaO·7Al2 O3 synthesized at 1500°C was analyzed by XRD and SEM. The results indicate that the main phase of samples synthesized is 12CaO·7Al2 O3 when holding time is over 30 min. The lattice constant increases and the preferred orientation decreases as synthesis time prolongs. The average grain size of samples is about 59 nm calculated by Scherrer formula, and it does not change with synthesis time. The synthesis time affects the micromorphology of samples greatly. There are more and bigger holes in samples synthesized for long time. The aspects mentioned above cause the alumina leaching ratio of 12CaO·7Al2 O3 to increase with the prolonging of synthesis time, but the rate of increase drops.